SYSTEM AND METHOD FOR ADVERTISING GOODS AND SERVICES USING A SHORT IDENTIFYING CODE (2013)
A system and method of providing advertising information from a database of advertising listings using a short, easy to remember alphanumeric identifying code associated each listing. The codes are promoted through various known advertising methods. A consumer, upon observing the ad and the code, can obtain additional information regarding the subject matter of the ad by accessing the system and entering the code. The system receives the request and the code from the consumer and transmits the listing of interest to the consumer. In order to keep the codes short while still providing a large number of listings, each code may be associated with multiple listings. The system may filter the listings associated with a requested code using various data, and may also transmit to the consumer a list of such listings from which the consumer may select the listing of interest.